Pengaruh Penggunaan Laboratorium Virtual Terhadap Penguasaan Konsep dan Kemampuan Berpikir Kreatif Siswa pada Materi Getaran dan Gelombang - Hermansyah Hermansyah; Gunawan Gunawan; Lovy Herayanti (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research aims to know the effect of using virtual laboratorial towards concept mastery and creative thinking ability of students on the material of vibrations and waves. This research is an experimental research that uses pretest-postest control group design. The population of this research is all grade VIII students of SMPN 1 Alas Barat in the academic year 2013/2014 and the sample of this research is grade VIII3 as experimental group and VIII4 as control group that determined by cluster random sampling technique. The instrument thet used to collect the data is test that made in terms of multiple choices and essay test. The data is analysed by statistical formula of N-Gain and t-test. The result of N-Gain of experimental group concepts mastery is 0,5% and control group is 0,2%. Meanwhile, the result of N-Gain of experimental group creative thinking ability is 0,3% and control group is 0,1%. The resultof t-test shows that tobtined of concepts mastery is 1,877 Ã¢â°Â¥ ttable is 1,671. Whereas, for creative thinking ability shows that tobtined is 1,998 Ã¢â°Â¥ ttable is 1,671. It means that there is a difference of concept mastery and creative thinking ability of students on the material of vibrations and waves. Therefore, it can be concluded that the use of virtual laboratorial has an effect towards concept mastery and creative thinking ability of students on the material of vibrations and waves.